ANALISIS STRATEGI BISNIS UNTUK MENINGKATKAN DAYA SAING - Efriano, Adi Galih; Rofiaty, Rofiaty (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The business activities of companies in their business operations are inseparable from the influence of their business environments. The current global competition has required companies to develop their business systems by planning management systems and renewable strategies. Those measures must be taken in order to achieve their vision and mission in the future, from which they will be able to compete as the changes come from sources beyond their control. The goal of this study is to formulate an appropriate business strategy for CV Srikandi for higher competitiveness. The data of this qualitative descriptive research was harvested from interviews and documentations at the Malang Cite-based company. This study finds that the most appropriate business strategy for the company is the W-T strategy found in the SWOT analysis. Here the company is advised to make improvements in marketing, human resource, finance, and operation in order to get higher competitiveness.